Antigen-based immunotherapy (AIT) for autoimmune and allergic disease. (August 2015) - MacLeod, Megan KL; Anderton, Stephen M
Highlights: AIT allows specific targeting of the cells that drive pathology in allergy and autoimmunity. AIT is a recognised treatment for human allergic disease. AIT can delete T cells and/or induce functional tolerance. AIT can modify previously activated T cells epigenetically. Abstract : Autoimmune and allergic diseases are major causes of morbidity. Antigen-based immunotherapy (AIT) is immunologically the most satisfying means of specifically targeting only those T cells driving disease, thereby inducing antigen-specific immune tolerance, with the lowest adverse risk profile. AIT is highly effective in rodent models of T cell-driven inflammation and is now in clinical trials. The range of approaches to applying AIT in the clinic prevents a consensus on the molecular basis for this form of tolerance. In particular, there has been a paucity of information on how pre-activated effector and memory T cells respond to AIT. New, advanced murine models of AIT are beginning to deliver such information at the cellular, biochemical, transcriptional and epigenetic levels.